Development of sample instructional materials in communication arts (English ) grade four of the University of the Philippines Integrated School - Valencia, Nora Q.
This paper consists of sample instructional materials for Communication Arts (English) Grade Four of the UP Integrated School (UPIS). The materials were developed within a conceptual framework that took into consideration not only the needs of the society and the needs of the learner, but the nature of language, the nature of language learning, and the basic characteristics of a functional communication arts program. The instructional materials consists of two lessons each for Units I to III, and one lesson each for Units IV and V, making a total of eight lessons.